Penggunaan Media Gambar Dalam Meningkatkan Minat Belajar Siswa Pada Pelajaran Fiqih Kelas VII Di MTs Aisyiyah Kota Binjai - Aisyah Rahma Fitri Tanjung; Nabila Syafinka Putri; M. Ilyasa Ramadhan (Yayasan Rahmat Islamiyah, 2023)
Learning media in the form of images is an intermediary tool used by educators in the teaching and learning process so that learning objectives can run well and can help students to increase interest in learning. This study aims to determine the application of media images in increasing students' learning interest in Fiqh lessons at MTs Aisyiyah Binjai City. This type of research is qualitative research, in which the researcher describes the application of media images in increasing students' interest in learning Fiqh at MTs Aisyiyah Kota Binjai through interviews as well as observation and documentation. The research subjects consisted of school principals, Fiqh teachers, and all students of class VII. The results showed that the teacher's strategy in using media images in increasing student learning interest in class VII Fiqh lessons at MTs Aisyiyah namely: carrying out the activity steps listed in the lesson plans, explaining material, providing material reinforcement materials such as textbooks, carrying out activities evaluation.